Spontaneous and indicated preterm delivery risk is increased among overweight and obese women without prepregnancy chronic disease. (1st April 2017) - Kim, SS; Mendola, P; Zhu, Y; Hwang, BS; Grantz, KL
Abstract : Objective: To investigate the independent impact of prepregnancy obesity on preterm delivery among women without chronic diseases by gestational age, preterm category and parity. Design: A retrospective cohort study. Setting: Data from the Consortium on Safe Labor (CSL) in the USA (2002–08). Population: Singleton deliveries at ≥23 weeks of gestation in the CSL (43 200 nulliparas and 63 129 multiparas) with a prepregnancy body mass index (BMI) ≥18.5 kg/m 2 and without chronic diseases. Methods: Association of prepregnancy BMI and the risk of preterm delivery was examined using Poisson regression with normal weight as reference. Main outcome measures: Preterm deliveries were categorised by gestational age (extremely, very, moderate to late) and category (spontaneous, indicated, no recorded indication). Results: Relative risk of spontaneous preterm delivery was increased for extremely preterm among obese nulliparas (1.26, 95% CI: 0.94–1.70 for overweight; 1.88, 95% CI: 1.30–2.71 for obese class I; 1.99, 95% CI: 1.32–3.01 for obese class II/III) and decreased for moderate to late preterm delivery among overweight and obese multiparas (0.90, 95% CI: 0.83–0.97 for overweight; 0.87, 95% CI: 0.78–0.97 for obese class I; 0.79, 95% CI: 0.69–0.90 for obese class II/III). Indicated preterm delivery risk was increased with prepregnancy BMI in a dose–response manner for extremely preterm and moderate to late preterm among nulliparas, as it was for moderate to late preterm delivery among multiparas. Conclusions: Prepregnancy BMI was associated with increased risk of preterm delivery even in the absence of chronic diseases, but the association was heterogeneous by preterm categories, gestational age and parity. Tweetable abstract: Obese nulliparas without chronic disease had higher risk for spontaneous delivery <28 weeks of gestation. Tweetable abstract: Obese nulliparas without chronic disease had higher risk for spontaneous delivery <28 weeks of gestation.